Application of E-Government in Public Service in Biawao Village, Gorontalo City - Srihandayani Suprapto; Irma B. Lolo (Borong Newinera Publisher, 2022)
This study aims to determine the application of E-Government in public services in Biawao Village, Kota Selatan District, Gorontalo City. The research method uses qualitative types. The results showed that the application of E-Government in public services in Biawao Village, Kota Selatan District, Gorontalo City was measured by 4 (four) indicators, namely indicators of benefits, efficiency, participation and transparency were not optimal. This can be seen from the minimal use of online-based public services, the low enthusiasm of the public in using online-based public services and the limitations on applications that are not able to answer the needs and complaints of people via online.